Bioelectronics at graphene–biofilm interface: Schottky junction formation and capacitive transitions. Issue 3 (5th November 2018) - Ray, Sanhita; Sen, Sayantani; Das, Alakananda; Bose, Anirban; Bhattacharyya, Anirban; Das, Avishek; Chattopadhyay, Sanatan; Singha, Shib Shankar; Singha, Achintya; Patra, Hirak K.; Dasgupta, Anjan Kr.
Abstract: We have used an interface of bacterial community and graphene that may provide a platform for tunable bioelectronic components. Graphene nanoplatelets were immobilized by using the establishment process of photosynthetic, purple non‐sulphur biofilm. While immobilized on metallic electrodes, DC current–voltage plot exhibited symmetric threshold voltage which is indicative of both‐way Schottky diode formation. The biomaterial itself demonstrated presence of convergence points in capacitive spectra on frequency axis, when AC amplitude was varied. Incorporation of graphene disrupted such points of convergence and increased the photopigment content in biofilms in response to it. Limiting the carbon source was found to diminish and ultimately reverse this effect. In summary, cross‐talk between the surface electron cloud of two‐dimensional (2D) graphene and biofilm, growing on a 2D surface, can lead to smart hybrid materials, which in turn can be exploited as bioelectronic components.